2023
DOI: 10.1039/d3qi00290j
|View full text |Cite
|
Sign up to set email alerts
|

Strong magnetic exchange coupling in Ln2 metallocenes attained by the trans-coordination of a tetrazinyl radical ligand

Abstract: A combination of high-performing lanthanide metallocenes and tetrazine-based radical ligands leads to a new series of radical-bridged dinuclear lanthanide metallocenes; [(Cp*2LnIII)2(bpytz•-)][BPh4] (where Ln = Gd (1), Tb (2), Dy (3)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
(114 reference statements)
0
5
0
Order By: Relevance
“…The Kramers nature of the ground state wave functions prevents their direct mixing, hence such species are nearly always EPR silent. 71 A similar effect due to an axial CF is expected for the Ho III complex (1) with an m J = ±8 quasi-doublet ground state and a sizable separation to the m J = ±7 excited states. However, a key difference in the Ho III case is that it is not a Kramers ion, meaning that the ±m J states can mix to the first order.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…The Kramers nature of the ground state wave functions prevents their direct mixing, hence such species are nearly always EPR silent. 71 A similar effect due to an axial CF is expected for the Ho III complex (1) with an m J = ±8 quasi-doublet ground state and a sizable separation to the m J = ±7 excited states. However, a key difference in the Ho III case is that it is not a Kramers ion, meaning that the ±m J states can mix to the first order.…”
Section: Resultsmentioning
confidence: 59%
“…This results in an isolated ground doublet with a maximal m J = ±15/2 projection and a large barrier to magnetization reversal. The Kramers nature of the ground state wave functions prevents their direct mixing, hence such species are nearly always EPR silent . A similar effect due to an axial CF is expected for the Ho III complex ( 1 ) with an m J = ±8 quasi-doublet ground state and a sizable separation to the m J = ±7 excited states.…”
Section: Resultsmentioning
confidence: 71%
“…For cis -structures, a coordination pocket with quadridentate coordination was common, whereas the ligand was almost in the same plane with a calculated dihedral angle (θ) of 7.249° (Figure S8). As for the trans -configuration, the ligand was severely distorted and not in the same plane (θ is 36.479°) when it exhibited tridentate coordination, affecting the symmetry of the complex. The local coordination models of three Dy III ions of 1 were then analyzed (Figure S9), where Dy1 and Dy2 or Dy1 i and Dy2 ions were connected via the Dy 2 O 2 configuration, and Dy1 and Dy1 i were connected via a CH 3 COO – . To rationally regulate the structure of 1 , the formation process was reasonably speculated based on the single-crystal data and coordination configuration (Scheme a).…”
Section: Resultsmentioning
confidence: 99%
“…Among Ln III ions, Dy III -based SMMs demonstrate many remarkable properties. , The magnetic properties of SMMs are closely related to the electron cloud distribution of metal ions. For oblate Dy III –SMMs, a strong axial crystal field (CF) and weak equatorial ligand field are required to balance the electron cloud distribution. , However, for multicore systems, the magnetic coupling is complex because of the different anisotropy of central ions.…”
Section: Introductionmentioning
confidence: 99%
“…Of additional interest in the field of Ln-SMMs is the possibility of modulating the SMM properties through exchange coupling with radical ligands, providing a chemically-encoded redox switch. [5][6][7][8] However, elucidation of the sign and magnitude of this coupling is challenging in most cases, due to the large unquenched orbital angular momentum of the lanthanoid ions of interest. Building on an early study from Caneschi et al, [9] we have recently reported elucidation of the exchange coupling between an Er(III) ion and the 3,5-di-tertbutylseminquinonate (dbsq *À ) radical ligand in the complex [ErTp 2 dbsq] (Tp À = hydro-tris(1pyrazolyl)borate) in a combined experimental and computational investigation.…”
Section: Introductionmentioning
confidence: 99%